Comparative Assessment of Urban Flood Risks due to Urbanization and Climate Change in the Turnhout Valley of Belgium - Alam, Md. Shahabul; Willems, Patrick; Alam, Md. Masud (ABC Journal of Advanced Research, 2014)
The combined effect of urbanization and climate change on catchment runoff has been drawing attention in the recent years to assess the impact of climate change on urbanizing catchments. There has been extensive development of paved areas within the city of Turnhout in Belgium in combination with several modifications of the neighbouring rivers. Moreover, the city authority has decided to encourage more densification of housing and industries within or next to the cores, which would lead to frequent overflows out of the existing combined sewer system. This combination leads to a faster flow of larger quantities of water which physically cannot be retained by the valleys over this region and thus causes increasingly frequent and harmful flood events affecting agricultural lands. The situation could be indisputably exacerbated under climate change scenarios. This study focuses on assessing the effects of urban development and climate change on flood risks in the downstream of Turnhout. For this study, a lumped conceptual hydrological model NAM was developed for generating runoff from the catchment. The CCI-HYDR perturbation tool, developed by Katholieke Universiteit Leuven, was applied to generate time series of future rainfall and evapotranspiration. The urban runoffs were obtained from the simulation of existing InfoWorks CS model under both current and climate change (A1B, A2, B1 and B2) scenarios. Rainfall-runoff was then uniformly distributed along the river reaches and urban runoff was applied as point source boundary conditions in the calibrated and validated MIKE 11 river flood model. Composite hydrographs with different return periods for all the boundary conditions were generated through extreme value analysis. The results show intensified and more frequent peak runoff resulting from combined effect of urbanization and climate change, in comparison to the individual effect of urbanization or climate change each. The increased peak runoff in the river due to heavy rainfall coinciding with development of paved surfaces within the city would lead to severe urban flooding when urbanization and climate change scenarios are accounted for.